Utilización de bloques nutricionales con la adición de tres niveles de harina de brócoli (Brassica oleracea) en la alimentación de cuyes (Cavia porcellus) en fase de crecimiento engorde, en la Provincia de Cotopaxi, Cantón Pujilí, Barrio El Tejar - Ganchala Casa, Darwin Rubén (2022)
This research study was carried out in ‘El Tejar’ neighborhood of the Pujilí Canton, Cotopaxi Province, where the use of nutritional blocks with the addition of 5%, 10%, and 15% of broccoli flour in the feeding of guinea pigs in the fattening growth phase was evaluated. 40 male guinea pigs with an average weight of 390 grams were used, which were distributed under a completely randomized design (CRD). The research lasted six weeks and the productive variables evaluated were feed intake, weight gain, and feed conversion. The food that was most accepted by the guinea pigs was T3 (addition of 15% broccoli flour) when registering a consumption of 272.68 g, observing a significant statistical difference (P=<0.0001). The highest weight gain was obtained in treatments T2 (addition of 10% broccoli flour) with 83.40 g and T3 (addition of 15% broccoli flour) with a value of 82.20 g. There was a significant statistical difference, (P=<0.0001). In the T2 treatment, the best utilization of food could be observed with a feed conversion of 3.30, reflecting that there was a significant statistical difference (P=<0.0001) in relation to the other treatments. The use of broccoli flour in the elaboration of nutritional blocks is a nutritional alternative that can be used by small and medium-sized guinea pigs producers, since it helps to cover the nutritional requirements of these animals, reducing the cost of maintenance and production in the fattening growth phase. fattening growth, especially in summer when forage is in short supply.